-9(-3x-1)=-45

Simple and best practice solution for -9(-3x-1)=-45 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9(-3x-1)=-45 equation:



-9(-3x-1)=-45
We move all terms to the left:
-9(-3x-1)-(-45)=0
We add all the numbers together, and all the variables
-9(-3x-1)+45=0
We multiply parentheses
27x+9+45=0
We add all the numbers together, and all the variables
27x+54=0
We move all terms containing x to the left, all other terms to the right
27x=-54
x=-54/27
x=-2

See similar equations:

| 1/8p=18 | | 10x2-7x-6=0 | | 31=-(-6+5x) | | (4x-20)-(x+15)=x | | 4(12x+5)=48x-7 | | -9=6–5(s+10) | | 180x+90×=84 | | 5x+38=2x-19 | | 1/9m=5 | | Y+x=84 | | 9=6–5(s+10) | | s+43=1 | | -3(4t-2)+6t=7t+-4 | | -8(p+6)=48 | | -3(4t-2)=6t=7t+-4 | | -8=2(x+7) | | -15x+-45=-45 | | -3=-q-1/3 | | 8(d+2)=58–6d | | t=2t+3.59 | | 42x-43=-42x+-43 | | 5x+12x-6=16x+10 | | 2(X–1)+8=4x-20 | | 6=10d-9d | | -9=-3(5+y)+15 | | -6=-6(6+x) | | 7x+4=3×+5 | | 2+5z=62 | | b/2+5=8 | | 7x-10=26+x | | 165-w=228 | | 3n=7n-6 |

Equations solver categories